Toward a humanized technology: a reinterpretation of Erich Fromm’ s humanistic peace psychology - Wang, Yun; Li, Peng; Liu, Wenyu (Frontiers in Psychology, 2026)
In contemporary society where technology has advanced significantly, the issues of war and peace are not only political or economic but also deeply tied to the structure of human psychology. Based on Erich Fromm’s humanistic psychology, this paper reexamines the adaptability and framework of peace psychology in the technological era. First, the paper explores the psychological roots of war, emphasizing that deep psychological mechanisms such as aggressiveness, idolization, and emotional numbness are key drivers of war. Second, the paper distinguishes between the concepts of “negative peace” and “positive peace,” proposing that positive peace should encompass positive psychological resources such as justice, love, and freedom, rather than merely the cessation of violent conflict. Furthermore, the paper analyzes the emotional coldness, numbness, and the aestheticization of war in the media brought about by technological alienation, revealing the erosion of the psychological foundation for peace by these technologies and proposing “humanized technology” as a solution. By emphasizing that technology should serve humanity’s empathy, creativity, and freedom, rather than alienation and control, this paper provides new perspectives for the theoretical innovation and practical development of contemporary peace psychology. The core contribution of this paper lies in the interdisciplinary integration of Fromm’s peace psychology with contemporary technological advancements, presenting strategies to address the impact of technology on individuals and society. Finally, the article provides important topics for future empirical research, including the psychological effects of emotional detachment and digital warfare, peace education in algorithmic environments, and the psychological and ethical studies of artificial intelligence and neural technologies.